Mister Exam

Other calculators


3x-5(2x+1)=3(3-2x)

3x-5(2x+1)=3(3-2x) equation

The teacher will be very surprised to see your correct solution 😉

v

Numerical solution:

Do search numerical solution at [, ]

The solution

You have entered [src]
3*x - 5*(2*x + 1) = 3*(3 - 2*x)
3x5(2x+1)=3(32x)3 x - 5 \left(2 x + 1\right) = 3 \left(3 - 2 x\right)
Detail solution
Given the linear equation:
3*x-5*(2*x+1) = 3*(3-2*x)

Expand brackets in the left part
3*x-5*2*x-5*1 = 3*(3-2*x)

Expand brackets in the right part
3*x-5*2*x-5*1 = 3*3-3*2*x

Looking for similar summands in the left part:
-5 - 7*x = 3*3-3*2*x

Move free summands (without x)
from left part to right part, we given:
7x=146x- 7 x = 14 - 6 x
Move the summands with the unknown x
from the right part to the left part:
x=14- x = 14
Divide both parts of the equation by -1
x = 14 / (-1)

We get the answer: x = -14
The graph
-24-22-20-18-16-14-12-10-4-8-60200
Sum and product of roots [src]
sum
-14
14-14
=
-14
14-14
product
-14
14-14
=
-14
14-14
-14
Rapid solution [src]
x1 = -14
x1=14x_{1} = -14
x1 = -14
Numerical answer [src]
x1 = -14.0
x1 = -14.0
The graph
3x-5(2x+1)=3(3-2x) equation